Neighbourhood approximation using randomized forests [Best Paper Award] - Konukoglu, Ender; Glocker, Ben; Zikic, D.; Criminisi, Antonio (Medical Image Analysis, 2013)
Leveraging available annotated data is an essential component of many modern methods for medical image analysis. In particular, approaches making use of the “neighbourhood” structure between images for this purpose have shown significant potential. Such techniques achieve high accuracy in analysing an image by propagating information from its immediate “neighbours” within an annotated database. Despite their success in certain applications, wide use of these methods is limited due to the challenging task of determining the neighbours for an out-ofsample image. This task is either computationally expensive due to large database sizes and costly distance evaluations, or infeasible due to distance definitions over semantic information, such as ground truth annotations, which is not available for out-of-sample images. This article introduces Neighbourhood Approximation Forests (NAF), a supervised learning algorithm providing a general and e cient approach for the task of approximate nearest neighbour retrieval for arbitrary distances. Starting from an image training database and a user-defined distance between images, the algorithm learns to use appearance-based features to cluster images approximating the neighbourhood structured induced by the distance. NAF is able to e ciently infer nearest neighbours of an out-of-sample image, even when the original distance is based on semantic information. We perform experimental evaluation in two di erent scenarios: i) age prediction from brain MRI and ii) patch-based segmentation of unregistered, arbitrary field of view CT images. The results demonstrate the performance, computational benefits, and potential of NAF for di erent image analysis applications.